Quantum light drives electrons strongly at metal needle tips - Heimerl, Jonas; Rasputnyi, Andrei; Pölloth, Jonathan; Meier, Stefan; Chekhova, Maria; Hommelhoff, Peter (Nature Physics, 2025)
Attosecond science relies on driving photoemitted electrons with the strong optical field of a laser pulse, which represents an intense classical coherent state of light. Bright squeezed vacuum is a quantum state of light that is also intense enough to drive strong-field physics. However, its mean optical electric field is zero, suggesting that, in a semi-classical view, electrons should not experience strong driving. The question arises if and how this quantum state of light can generate signatures of attosecond dynamics in strong-field photoemission. Here we show that the key signatures of strong-field physics—the high energy plateau and subsequent cut-off—also appear under driving of a needle tip by bright squeezed vacuum, but only when we post-select electron energy spectra on the individual photon number of each pulse. When averaging over many shots, we observe broad energy spectra without a plateau. This suggests that electrons driven by bright squeezed vacuum behave as if driven by an ensemble of coherent states of light. Our findings bridge strong-field physics and quantum optics, offering insights into bright squeezed vacuum and other quantum light states, and suggest the use of strongly driven electrons as quantum light sensor
Keywords: Attosecond science; Matter waves and particle beams; Single photons and quantum effects; Surfaces; interfaces and thin films